Thematic instruction on the wheels of indigenous stories: A creative approach to enhancing foundational learning outcomes - Tetteh, Agnes Afua; Tawiah – Mensah, Joyce Esi; Bonney, Ebenezer Appah; Akosah, Ernest Frimpong; Kafu, George Yao (Journal of Interdisciplinary Studies in Education, 2025)
This study explores the integration of indigenous stories into thematic teaching in Ghanaian kindergartens to enhance foundational learning. Guided by Rogoff’s sociocultural theory and participatory action research, data were collected from four schools in the Awutu-Senya East Municipality through observations and interviews. The findings show that while indigenous stories foster engagement, identity, and literacy, their use is limited due to teachers’ lack of storytelling skills, cultural knowledge, and language fluency. The study recommends curriculum revisions, teacher training, and leveraging professional learning communities to support integration. Emphasizing indigenous narratives can strengthen early learning experiences, and further research is needed to evaluate their broader educational impact.